(untitled) (Revista Lusófona de Educação, 2024)
The article examines the role of digital resources in the realization of the Sustainable Development Goals (SDGs) and in building a sustainable future. It highlights the importance of understanding their context and the challenges associated with their achievement, and highlights the potential of digital technologies, along with a review of the most relevant digital resources. The article identifies the barriers and challenges that hinder the effective use of digital resources in the implementation of the SDGs and the impact of these resources on the process of achieving the goals. It also highlights the importance of investing in training and development of digital skills, promoting research and technological innovation, and fostering collaboration and exchange of good practices at the international level. There is significant development on the future potential of digital resources and recommendations are provided to promote their effective use in the realization of the SDGs. Successful implementation of the SDGs requires coordinated action at the global level, and digital resources are presented as valuable tools to drive progress towards these goals. Keywords: Technology; Digital resources; Innovation; Sustainability; Sustainable Development Goals.